Vpliv epidemije COVID-19 na program rehabilitacije za otroke z motnjo v razvoju - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2021)
Background: In early March 2020, with a rapid increase in the number of patients with SARS-CoV-2 (COVID-19) infection, the World Health Organisation declared a pandemic. In addition to stopping public life, the Government of the Republic of Slovenia also ordered the cessation of all non-essential forms of treatment and rehabilitation, the closure of care and education programs for children, including those with impaired functional abilities. We were interested in what solutions for continuing rehabilitation programs the experts working with children with developmental disabilities found abroad. Further, we wanted to know whether a deterioration in functional status was found in the population of these children who had a smaller volume of rehabilitation programs. Methods: In the PubMed database, we used specific keywords to find all the articles that had been published since the beginning of the epidemics. We considered the following inclusion criteria: articles in English; original research on the impact of the COVID-19 epidemic on rehabilitation programs, on children with developmental disabilities and their parents. Results: We found 14 articles, then excluded eight that did not meet the inclusion criteria. The authors of the selected articles focused on the consequences of closure of rehabilitation programs and the impact on parental and child well-being, parental mental health, telerehabilitation efficacy, and risk assessment for inpatient treatment due to health complications after botulinum toxin spasticity treatment in children with cerebral palsy. We did not find any research on the deterioration of the functional status due to the reduced program. Conclusion: The authors are already reporting the consequences of the epidemics, especially on parents' mental health. We can also expect a deterioration of functional status of children in the future, but there is no data in the available literature yet. In the future, we propose close monitoring of the functioning of children with disabilities and their parents. We also believe that it is necessary to develop telerehabilitation programs in accordance with the goals from the activities and participation domain, and to assess their effectiveness.
Keywords: Child; COVID-19; Developmental Disabilities; developmental disorders; motnje v razvoju; otrok; rehabilitacija; rehabilitation